Լիբանանում շիական գործոնի ուժեղացման հարցի շուրջ (1970-1980-ական թվականներ) - Հարությունյան, Լիլիթ («Զանգակ - 97»)
Lebanese Shi'i communily plays a spccial and very important role in the confessional political system ol'Lebanon. Beginning from 1970's the Shi'i Community becamc already the largest Community of Lcbanon although it continued to be the most ignored one. In 1970-1980's the Lcbanesc Shi'i Community was cxperiencing а whole social, political and economic rcnaissance due to which mostly grew the Shi'is role in the Lebanese political arena. In this case the Shi'is headed the front of Israel resistant forces in Lebanon.
Keywords: Պատմություն; Քաղաքականություն